P2Y1R Ligation Suppresses Th17 Cell Differentiation and Alleviates Colonic Inflammation in an AMPK-Dependent Manner - Chang, Yao-Yao; Huan, Qiu-Chan; Peng, Jiao; Bi, Wen-Chun; Zhai, Li-Xiang; Chen, Yan; Lamb, Jonathan R.; Shen, Xiang-Chun; Bian, Zhao-Xiang; Wu, Hai-qiang; Cheng, Yong-Xian; Xiao, Hai-Tao (Frontiers in Immunology, 2022)
P2Y1 receptor is a G-protein-coupled receptor that plays a critical role in the immune response of inflammatory bowel diseases. However, its regulatory effects on CD4+ T cell response have not been fully elucidated. The study aimed to characterize the role of P2Y1R in Th17 cell differentiation and colonic inflammation. Our results demonstrated that P2Y1R was significantly increased in the splenocytes of colitic mice, which was positively associated with the expression of RORγt and IL-17A. P2Y1R deficiency significantly ameliorated DSS-induced colitis and its Th17 responses. In parallel, P2Y1R deficiency greatly impaired the differentiation of Th17 cell, down-regulated the mRNA expression of IL-17A and RORγt, and protein expression of RORγt in vitro. More importantly, it was found that P2Y1R deficiency markedly increased AMPK phosphorylation of Th17 polarized CD4+ T cells, and antagonist of AMPK significantly reversed the inhibitory effect of P2Y1R deficiency on Th17 cell generation in vivo and in vitro. Overall, these findings demonstrated that P2Y1R deficiency could suppress Th17 cell differentiation in an AMPK-dependent manner to ameliorate colitis, and P2Y1R can act as an important regulator of Th17 cell differentiation to control colonic inflammation.